2021
DOI: 10.3389/fpsyt.2021.640575
|View full text |Cite
|
Sign up to set email alerts
|

Mood Symptoms, Suicide, and Associated Factors Among Jimma Community. A Cross-Sectional Study

Abstract: Background: The global burden of mental health problems is high and is predicted to rise. At present, mood symptoms are the foremost common psychological problems worldwide, yet little is known regarding their magnitude and associated factors in developing countries. Therefore, this study aimed to assess the magnitude and associated factors of anxiety, depressive, manic symptoms, and suicidal behavior among the rural Jimma community, Ethiopia.Methods: A community-based quantitative cross-sectional survey was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Highly protective behavior (AOR = 2.2, 95% CI: 1.5–3.3) and perceived risk behavior (OR = 3.7, 95% CI: 1.5–12.4) predict higher anxiety among the general population ( 42 ) but not among healthcare professionals ( 58 ). Displacement due to conflict ( 80 ), lack of emotional support from family or society ( 46 , 66 , 79 , 97 ), and experiencing discrimination or racism (AOR = 5.02, 95% CI: 1.90–13.26) ( 84 ) were significantly associated with COVID-19 related anxiety. Reading or watching COVID-19 related news via media or internet sources was associated with increased anxiety ( 27 , 43 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly protective behavior (AOR = 2.2, 95% CI: 1.5–3.3) and perceived risk behavior (OR = 3.7, 95% CI: 1.5–12.4) predict higher anxiety among the general population ( 42 ) but not among healthcare professionals ( 58 ). Displacement due to conflict ( 80 ), lack of emotional support from family or society ( 46 , 66 , 79 , 97 ), and experiencing discrimination or racism (AOR = 5.02, 95% CI: 1.90–13.26) ( 84 ) were significantly associated with COVID-19 related anxiety. Reading or watching COVID-19 related news via media or internet sources was associated with increased anxiety ( 27 , 43 , 45 , 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…Depression scores were significantly correlated with overall anxiety ( 14 , 35 , 40 , 50 ) and sleeplessness ( 14 , 54 ). Overall depression was significantly associated with symptoms of mania (AOR = 4.3, 95% CI: 1.71–11.02) ( 84 ) and Fear of Covid scores ( r = 0.5, p < 0.001) ( 77 ). Depression-related symptoms included reports of boredom ( 94 ), poor mood ( 82 ), loneliness ( 91 ), loss of interest ( 101 ), total emotional exhaustion ( 77 , 78 ) and suicidal ideation or behavior ( 71 , 84 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty one percent of the South African orphaned adolescents in secondary school had depressive symptoms (11), Ethiopian health survey indicated that the prevalence of depressive episode among adults is 9.1% (12). In Addis Ababa 36.4% (13), Tesfaye et al in Jimma found 13.1% among community (14), 36.2% in Aksum Tigray (15) and 28% of adolescents in Jimma were having depressive symptoms (16).…”
Section: Introductionmentioning
confidence: 99%